2008
DOI: 10.1017/s1742758408959646
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical factors associated with resistance to Maruca vitrata (Lepidoptera: Pyralidae) in short-duration pigeonpea

Abstract: The spotted pod borer Maruca vitrata (Geyer) is known for its economic importance throughout its geographical distribution because of its destructive nature to reproductive parts of several grain legume crops including pigeonpea. In view of the importance of the pest, the present study was carried out on the association of different morpho-chemical traits with resistance/susceptibility to M. vitrata at the International Crops Research Institute for the Semi-Arid Tropics, Patancheru, India. Trichome length and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
7
16
0
Order By: Relevance
“…Pigeonpea pod walls with more wax, total phenols and less reducing and non-reducing sugars and total amino acids ( Table 2) suffers less pod and grain damage by pod fly [47]. Similar findings have been reported for resistance to pod fly [26,55] and H. armigera in wild species [31], and to M. vitrata in cultivated pigeonpea [56].…”
Section: Biochemical Basis Of Resistance To Insectssupporting
confidence: 72%
“…Pigeonpea pod walls with more wax, total phenols and less reducing and non-reducing sugars and total amino acids ( Table 2) suffers less pod and grain damage by pod fly [47]. Similar findings have been reported for resistance to pod fly [26,55] and H. armigera in wild species [31], and to M. vitrata in cultivated pigeonpea [56].…”
Section: Biochemical Basis Of Resistance To Insectssupporting
confidence: 72%
“…In present study it was found that protein content in pods and flowers were significantly higher (29.46 and 22.46%) in susceptible YL 305 compared to moderately resistant Long Red Mollika (21.00 and 15.17%) ( Table 5). Sunitha et al (2008) also observed similar trend that protein content in pods was significantly higher (25.5%) in susceptible ICPL 88034 compared to resistant ICPL 98003 (16.5%) against the M. vitrata in short duration pigeonpea cultivars. Phenol and sugar compounds in the flower and green pods of the yard long bean are not found to contribute resistance against the insect M. vitrata (Table 5).…”
Section: Resultssupporting
confidence: 70%
“…A significant correlation between trichome length and per cent pod damage could not be observed in the study. Sunitha et al (2006) however, ha d obser ved significa nt negative correlation (-0.097) between trichome length on pods and pod borer damage in pigeon pea. Anaswar a. T he lowest trichome density was recorded in PKM-1 (16.34/6.25 mm 2 ), followed by Bhagyalekshmi, Lola, IC 52105, EC 300039, IC 20645, IC 20431, VellayaniJyothika and Palakkadanthandanpayar with 17.34, 18.34, 18.67, 27.34, 32, 33, 39.34 and 49.34 trichomes per 6.25 mm 2 , r esp ectively.…”
mentioning
confidence: 88%